Análise da produção do espaço urbano do município de São Pedro/SP : um caso de polinucleação - Fracassi, Priscila Carrara (2011)
The current study examines the production of urban space in São Pedro SP, considering that it occurs in a very peculiar way, where urban spaces spread on countryside in search for region's natural amenities, creating an urban scenery discontinuous and polynuclear. Defined by Town Guideline Plan as Urban Zone outside the headquarters of the Town (Z10), polynuclear areas results from the articulation of certain persons who appropriate the spaces in order to enjoy the rent of land, thereby reproducing the capitalist relations based the super-exploitation of man and environment, not worrying about the impacts resulting from these uses. Among the most active agents of this process are the Property Developers and the State. In the case of the municipality of São Pedro there is another important agent linked to social behavior: tourism. Thus, for the feasibility study were carried out research of the historical and socio-spatial features of this urban agglomeration and literature review on the subject. Moreover, the research also made use of data obtained in field studies, examination of existing urban laws in the three levels of government documents and other means. Finally the effectiveness of analysis and systematization of the data, using the concept of Spatial Deconstruction, allowed a spatial reading of urban expansion in different perspectives, highlighting the impacts to the natural or anthropic old. Such reading of the space intended to contribute for the implementation of policies related to the municipal planning and management, as well as enabling the ordering of the territory in its uniqueness to reverse the impacts generated by the process of Spatial Deconstruction for the reestablishment of the Renaturation.